Conductor sag comparison for 132 kV overhead transmission line improvement in Malaysia - H. M. Luqman; M. N. R. Baharom; N. A. M. Jamail; N. A. Othman; R. Abd. Rahman; M. F. M. Yousof; Irshad Ullah (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents conductor sag comparison for 132 kV overhead transmission line improvement in Malaysia. Increasing industrialization and population growth around the world demands higher electricity supply. Power generation has yet to decline but transmitting sufficient electricity to consumers is worrisome due to scarce land space occupied by rapid urbanization. Hence reconductoring method was chosen to improve existing 132 kV overhead transmission line in Malaysia. A group of selected conductors were chosen for comparison where the high temperature low sag conductor stood out the most producing up to 40% sag reduction. This paper focuses on providing conductor alternatives to improve maximum sag of lowest conductor to ground for 132 kV transmission line in Malaysia in accordance to her climate and geographical factor.